2015
DOI: 10.1097/md.0000000000002150
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Involvements of Immunoglobulin G4-Related Sclerosing Disease

Abstract: To investigate clinical and radiological features of IgG4-related disease (IgG4-RD) patients with intrathoracic involvement.A prospective cohort study was performed and IgG4-RD patients were enrolled from January 2011 to March 2015 in Peking Union Medical College Hospital, in which the clinical and radiological characteristics of IgG4-RD patients with intrathoracic involvement were summarized.Out of total 248 cases with IgG4-RD, 87 cases had intrathoracic lesions, including 58 male cases and 29 female cases, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 22 publications
4
56
1
Order By: Relevance
“…3 Zen et al reported that eight of nine patients with the nodular type had resection with no recurrence of pulmonary lesions. One case of the nodular type improved with corticosteroid treatment.…”
Section: Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Zen et al reported that eight of nine patients with the nodular type had resection with no recurrence of pulmonary lesions. One case of the nodular type improved with corticosteroid treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…16 Other intrathoracic manifestations include involvement of the pleura, pericardium, vasculature (the aorta, coronary arteries), and hilar and mediastinal lymph nodes. 3,5 Hilar and mediastinal lymphadenopathy, usually bilateral, is the most common intrathoracic finding and has been reported in 52.9-78.3% of patients. 3,5 IgG4-RD pleural disease presents alone or concurrently with parenchymal disease.…”
Section: 4 Radiologymentioning
confidence: 99%
See 3 more Smart Citations